FORMULATION AND EVALUATION OF BILAYER TABLET OF CANDESARTAN AND HYDROCHLOROTHIAZIDE FOR THE TREATMENT OF HYPERTENSION - pateriya, ankit (Journal of Drug Delivery and Therapeutics, 2013)
The main purpose of this study was to design bilayered sustained release tablet of Candesartan and Hydrochlorothiazide to provide renoprotection in hypertension. The bilayered tablet was prepared by using super disintegrant Cross Carmellose,starch sodium glycolate,crosspovidone for Hydrochlorothiazide to provide its immediate release and Candesartan was made sustained released by using HPMC K4,K15 polymer.lactose is used as diluents. The prepared different layer were characterized by different parameters like angle of repose, bulk density, tapped density, compressibility index, moisture content .The prepared bilayered tablet was characterized by physical and chemical parameters such as tablet thickness, hardness, diameter, weight variation, drug content, friability and in vitro drug release. The present studies concluded that bilayered tablet of Candesartan and Hydrochlorothiazide is novel approach to prevent hypertension.